2011
DOI: 10.2147/opth.s22879
|View full text |Cite
|
Sign up to set email alerts
|

Torsional ultrasound mode versus combined torsional and conventional ultrasound mode phacoemulsification for eyes with hard cataract

Abstract: Purpose:To compare torsional versus combined torsional and conventional ultrasound modes in hard cataract surgery regarding ultrasound energy and time and effect on corneal endothelium. Settings: Kasr El Aini hospital, Cairo University, and International Eye Hospital, Cairo, Egypt. Methodology: Ninety-eight eyes of 63 patients were enrolled in this prospective comparative randomized masked clinical study. All eyes had nuclear cataracts of grades III and IV using the Lens Opacities Classification System III (LO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
2
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 11 publications
1
24
2
2
Order By: Relevance
“…High CDE reading is equated with statistically significant corneal endothelial cell loss with one surgeon, one technique and one setting 17,18. Fakhry and El Shazly have shown that with an increase in the density of the nuclei there is an increase in the CDE 19. CDE in our study was less than the longitudinal and the torsional modality in the study by Fakhry and El Shazly.…”
Section: Discussioncontrasting
confidence: 45%
“…High CDE reading is equated with statistically significant corneal endothelial cell loss with one surgeon, one technique and one setting 17,18. Fakhry and El Shazly have shown that with an increase in the density of the nuclei there is an increase in the CDE 19. CDE in our study was less than the longitudinal and the torsional modality in the study by Fakhry and El Shazly.…”
Section: Discussioncontrasting
confidence: 45%
“…Torsional and transversal phaco modes are the results of these technological advances. Several studies have confirmed and reported the superiority of torsional phaco over longitudinal phaco in terms of needle time, chatter, followability, corneal edema, and corneal endothelium 1,5,712,19,20. However, to date, only one study has compared longitudinal, torsional, and transversal phaco 5.…”
Section: Discussionmentioning
confidence: 99%
“…Особенно высок риск осложнений при удалении плотного хрусталика [4]. В этом случае большое значение имеют не только мануальные навыки хирурга, но и гидродинамические и ультразвуковые настройки прибора, которые должны строго соответствовать особенностям хирургического подхода, используемого конкретным хирургом [5][6][7][8]. Соответствие настроек тем манипуляциям, которые присущи врачу, обеспечивает безопасность и эффективность процедуры.…”
Section: актуальностьunclassified
“…При неправильно подобранных настройках существенно возрастает риск травматизации окружающих тканей: радужки, цилиарного тела, капсульного мешка и роговицы [4,9,10]. Если повреждение радужки или капсульного мешка чаще приводит к серьезным интраоперационным осложнениям, то травма эндотелия роговицы чревата декомпенсацией состояния роговицы в послеоперационном периоде [1][2][3][4][5][6][7][8][9][10][11][12][13]. Послеоперационная кератопатия чаще всего связана с избыточной травмой эндотелия в ходе операции [13,14].…”
Section: актуальностьunclassified